A 3D simulation of a neutrino-driven supernova explosion aided by convection and magnetic fields. (14th August 2020) - Müller, Bernhard; Varma, Vishnu
ABSTRACT: We study the impact of a small-scale dynamo in core-collapse supernovae using a 3D neutrino magnetohydrodynamics (MHD) simulation of a 15 M⊙ progenitor. The weak seed field is amplified exponentially in the gain region once neutrino-driven convection develops, and remains dominated by small-scale structures. About 250 ms after bounce, the field energy in the gain region reaches 50 per cent of kinetic equipartition. This supports the development of a neutrino-driven explosion with modest global anisotropy, which does not occur in a corresponding model without magnetic fields. Our results suggest that magnetic fields may play a beneficial subsidiary role in neutrino-driven supernovae even without rapid progenitor rotation. Further investigation into the nature of MHD turbulence in the supernova core is required.